Interfacial magnetism in La0.7Sr0.3MnO3/LaNiO3 ultrathin superlattices. (13th July 2018) - Das, Sujit; Ghosh, Sayandeep; Pramanik, Prativa; Joshi, Deep Chandra; Thota, Subhash
Abstract: We report a detailed study of the structural and magnetic properties of pulse laser deposition grown superlattices (SLs) comprising of metallic ferromagnet La0.7 Sr0.3 MnO3 (LSMO) and paramagnet LaNiO3 (LNO) with the stacking order [(LSMO) d /(LNO) t ]15 ( d = 3.3 nm, t = 1.5 nm, 3 nm, 5 nm) on (1 1 1) and (0 0 1) − oriented SrTiO3 (STO) single crystal substrates. The x-ray reflectivity data and diffraction of SLs reveal the well-defined smooth and periodic nature of the SLs. The reciprocal space mapping provides the evidence of coherently strained epitaxial layers of the perovskite structures with long-range periodicity. The [(LSMO)3.3 /(LNO)3 ]15 SL on STO (1 1 1) exhibits a positive exchange-bias effect, which indicates the induced-magnetization with interface driven antiferromagnetic coupling in (1 1 1)-stacking. The robust magnetic ordering was observed for a SL grown on (1 1 1)-oriented STO as compared to the (0 0 1) stacked SLs. Beyond 1.5 nm thickness of LaNiO3, all of the above anomalous magnetic characteristics of SLs seizes away. The interface induced magnetism in the LNO layers was discussed using the temperature and magnetic field dependence of magnetization measurements.